Estimation of drought resistance in various by origin genotypes of buckwheat (Fagopyrum esculentum Moench.) - Тригуб, О. В.; Ляшенко, В. В. (Scientific Progress & Innovations, 2012)
The article deals with studying of collection samples by fruitful characteristics and morphological indicators in contrast conditions of environment. The hydrothermal coefficient was used as an additional index of cultivation conditions. Tolerance degree to action of extreme conditions of various characteristics of a vegetative organism is defined. Among studying group of buckwheat the genotypes have been picked out with the improved ability to adaptation in enough droughty conditions which are valuable initial material for selection of highly productive grades with considerable potential of stability to a drought.